Paradise library - Muhamad Deris, Nuratiqah; Zalzala, Nur Ain Najwa; M Said, Salasiah (Universiti Teknologi MARA, Kedah, 2017)
Information agency serves different types of users. Each of users has their own preference while searching for the information. There is a need for libraries, to cater the user’s need to make sure they are feeling comfortable while in a library. Paradise Library is a new design for those who seek for calm and peaceful place for rest and gaining new ideas. The problem arise in a library commonly regarding to the save space for the shelves, chair and many more. Other than that, user easy to feel bored with the same decoration in a library. In future, this library is able to invent the new concept and design for the library design and building. The novelty and uniqueness of this Paradise Library is library is free to decorate the space in order to make it more interested and easy to retrieve materials. Users also can get advantage from this Paradise Library because it gives peaceful and calm design.